Female Saudi nursing student perspectives on pursuing a career in home healthcare: a qualitative study - Wafa Almegewly; Taghreed Alotaibi; Savvato Karavasileiadou (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Despite the fact that the number of patients seeking home healthcare in Saudi Arabia is rising, this speciality confronts significant obstacles. This qualitative, descriptive phenomenological study investigates views, feelings and attitudes of nursing students practicing in home healthcare and how they perceive it as a future career. Data were gathered during five face-to-face focus group interviews of five students each (a total of 25 students) and analysed using thematic analysis. It was found that the majority of students did not perceive home healthcare as a viable career option compared to working in a hospital. They vacillated due to the nature of the work, safety concerns, working demands, the invariability of health cases, and a lack of opportunities for professional development. Nevertheless, some nursing students were amenable to pursuing a career in home healthcare due to the less working hours, sense of autonomy, and ability to provide holistic care and educate patients and their families. Population awareness programs are needed to overcome cultural barriers, increase student motivation, and ultimately bolster the number of certified nurses working in home healthcare.